The Stably-Stratified PBL Generated by Les - Filho, Edson P. Marques; Rizza, Umberto; Karam, Hugo A.; Carvalho, Jonas C.; Pereira, Maxsuel M. R. (Ciência e Natura, 2007)
The stably-stratified PBL generated by LES